Start-ups in the Sultanate of Oman: Between Reality and Aspiration - Al-Hammadi, Mohamed Hassan Ali; Al-Rahbiya, Ohood Talib Said (Journal of Ecohumanism, 2024)
Start-ups have received the necessary attention in the Omani legislator’s mindset through high-level speeches (2020–2023) that prioritize innovative and technical project implementation. This emphasis stems from their importance in enhancing innovation indicators and positioning the Sultanate in advanced global ranks. The technical Start-ups offer added market value that may support the growth of the economy, contribute to the implementation of sustainable development strategies, enhance global commercial competitiveness, facilitate commercial transactions, improve productivity in industrial sectors, and keep up with the Fourth Industrial Revolution and the developments in artificial intelligence applications based on the knowledge economy. This is achieved through activating a strong partnership between the public and private sectors to support industrial and productive sectors, increase entrepreneurial activity in businesses, and thrive on both local and international levels. These Start-ups represent key opportunities for social and economic growth, generating job opportunities for skilled national professionals and aiming to achieve social welfare. Accordingly, the Omani legislator has sought to encourage research and investment in technology and innovation fields, considering Start-ups as one of the sources of non-oil national income diversification, as adopted in Oman Vision 2040. This vision underscores the importance of organizing the work of Start-ups and creating legislative policies to address their legal and financial challenges. The study focuses on identifying the legal framework for Start-ups in Oman. The study is divided into two sections: the first discusses the legal nature of Start-ups, while the second examines the emerging trends to empower them. The study concludes with several findings and recommendations, the most notable of which is the need for the Omani legislator to establish the legislative and regulatory frameworks for Start-ups in line with the country’s economic policy to achieve sustainability according to the 2040 economic vision.